2017
DOI: 10.7557/1.6.1.4085
|View full text |Cite
|
Sign up to set email alerts
|

Speaker self-profiling through discursive indexation and syntactic encoding in Spanish radio talk

Abstract: ABSTRACT. Syntactic and discursive choices in context constitute resources for the interactional profiling of the direct participants. This study analyzes the frequencies with which speakers index themselves, as well as the syntactic functions they tend to accord themselves when doing so, in a corpus of Peninsular Spanish radio discourse featuring a variety of textual genres and speaker socioprofessional identities. The analysis is restricted to indexations of the singular first person in central syntactic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Previous research studies on subject and object variation found similar results regarding the omission of pronominal subject (Aijón Oliva and Serrano 2013) and person object (Aijón Oliva 2017a, 2017b; Serrano 2017a, 2017b) variants 2…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Previous research studies on subject and object variation found similar results regarding the omission of pronominal subject (Aijón Oliva and Serrano 2013) and person object (Aijón Oliva 2017a, 2017b; Serrano 2017a, 2017b) variants 2…”
Section: Resultssupporting
confidence: 52%
“…Spanish has an objective conjugation system (Llorente and Mondéjar 1974, Aijón Oliva 2006: 173–174). Clitics should not be considered to be personal pronouns but should instead be seen as agreement morphemes due to their atonicity, strict adjacency to verbs, and ability to co-occur with coreferential tonic pronouns and noun phrases in the same clause (Aijón Oliva 2017b). The ability to achieve pronominal indexation by clitics is a formal property of objects in Spanish (García-Miguel 2015: 207).…”
Section: Theoretical Background: Cognition and Discourse Stylementioning
confidence: 99%